Price clusters and stock price stability - Kordlouie, Hamid Reza; Ebrahimi, Mehrnoush; Dehkolani, Narges Mohseni; Kolaei, Azam Zare Jafar (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Understanding the factors affecting stock return volatility, for analysts, investors and company executives, it is critical. In this study, using a traditional approach, we identify the factors influencing volatility and how price friction is formed on stock price stability, and in particular, examining the clustering test for price increases. This study was carried out by examining the price clusters and stock price stability in the stock market and the OTC market between 2009 -2010. Econometric software was used to investigate the research variables. In this study, we tried to study stock price volatility in proportion to stock price clusters. Research findings showed; there is no significant relationship between stock price volatility and price clusters in the OTC market and the stock market.